Effects of lipopolysaccharide (LPS) challenge on antioxidant capability of broiler chickens - GAO, YU-YUN; CHEN, LI-ZHEN; ZHANG, JIE; FAN, QIAN; XU, LI-HUI; HUANG, YI-QIANG; WANG, CHANG-KANG (Indian journal of animal sciences, 2018)
This study was designed to investigate the effects of lipopolysaccharide (LPS) challenge on antioxidant capability (superoxide dismutase, SOD; catalase, CAT; glutathione peroxidase, GPX; and reduced glutathione to oxidized glutathione, GSH/GSSG) and induce the model of immunological stress in broiler chickens. Day-old, yellowfeathered broilers (140) were randomly assigned to 2 treatments with 7 replicates of 10 chicks each. At day 21, 23, 25 and 27, chicks were injected with LPS and blood samples were collected after 24 h. Chicks (2) from each replicate were killed, and liver and jejunum samples were collected. The activities and gene expression of SOD, CAT, and GPX, were determined. The results showed that LPS challenge reduced serum SOD at day 22 and 26, serum CAT at day 24, 26, and 28, and serum GPX at day 26. LPS challenge decreased liver SOD, liver GPX, liver GSH/GSSG ratio at day 26 and 28. LPS challenge also decreased jejunum SOD at day 26, and jejunum CAT, GPX and GSH/GSSG ratio at day 26 and 28.The expressions of liver CAT, liver GPX1, and jejunum SOD1 were down regulated at day 26. The expressions of jejunum CAT, and jejunum GPX1 were down regulated at day 26. Meanwhile, LPS reduced the expression of liver SOD1 at day 22 and the expression of jejunum GPX1 at day 28. In conclusion, three times of LPS challenge could result in serious oxidative damage and induce immune stress model.